Imperfect Information Equilibrium, Existence, Configuration and Stability - Bo Axell (The Research Institute of Industrial Economics (IUI), 1980)
In this paper we examine the stability properties of price dispersion equi1ibrium in a market where individuals and firms have to make efforts to collect information about the prices charged by firms and demand resulting from consumer behavior. The households are searching according to sequential stopping rules and the firms are making experiments in order to find out their demand curve. We show that the price dispersion equilibrium in such a market is stable.
Keywords: C70; D11; D21; 330; Consumer and firm behavior; Imperfect information; Price equilibrium